Pārttipan̲ kan̲avu - Kalki (Sufiya Publications, 2022)
Novel on the dream of Parthipan, a fictional Chola king and his son Vikraman's attempts to attain independence from the Pallava king Narasimhavarman I, who ruled South India from 630-668 AD.; previously serialized in Kalki, a Tamil magazine
Historical novel
Keywords: Historical fiction; Tamil; Narasimhavarman; Narasimhavarman - I - King of Kanchi - active 630-668; Fiction